A fully biodegradable PE wrapping film and its preparation process

By designing a fully biodegradable hierarchical structure in the PE wrapping film and adding degradation masterbatch, the problems of poor biodegradability and insufficient puncture and tear resistance in traditional PE wrapping films are solved, and efficient biodegradation and improved mechanical properties are achieved.

CN119348267BActive Publication Date: 2025-04-08上海森韦得实业有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411931945.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Due to poor biodegradability, traditional PE wrap films lead to white pollution problems. At the same time, their puncture and tear resistance are insufficient, which cannot meet the needs of large-scale applications.

Method used

The design of a fully biodegradable PE wrapping film is adopted, including the outer layer, the middle layer and the inner layer. Degradation masterbatches are added to each layer, made of PHA, cellulose nanofibers, algae powder, etc. The porosity and mechanical properties of the material are improved by foaming and adding nucleating agents.

Benefits of technology

The PE wrapping film is improved to resist puncture and tear resistance, and at the same time accelerates its biodegradation rate, so that the wrapping film can degrade by more than 90% within 12 weeks, achieving full biodegradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of packaging materials, and specifically discloses a fully biodegradable PE wrapping film and its preparation process. A fully biodegradable PE wrapping film comprises an outer layer, a middle layer and an inner layer which are laminated in sequence; the outer layer comprises the following raw materials: No. 1 LLDPE, LDPE, an opening agent, a lubricant, and a degradation masterbatch; the middle layer comprises the following raw materials: No. 2 LLDPE, LDPE, MLLDPE, and a degradation masterbatch; the inner layer comprises the following raw materials in weight percentage: No. 3 LLDPE, LDPE, a biodegradable thickening masterbatch and a degradation masterbatch; the degradation masterbatch comprises the following raw materials in weight parts: 30-50 parts of PHA, 10-16 parts of cellulose nanofibrils, 2-3.5 parts of algae powder, 1-2 parts of glycerol, 1-2 parts of a foaming agent, and 0.1-0.5 parts of a nucleating agent. The PE wrapping film of the present application has the advantages of strong tensile resistance and puncture resistance, easy degradation, fast degradation speed, and complete degradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of packaging materials, and more specifically, to a fully biodegradable PE wrapping film and a preparation process thereof. Background Art

[0002] Stretch film, also known as "stretch film", is a new type of self-adhesive wrapping packaging material. It is widely used in combined wrapping packaging of industrial products due to its excellent properties such as high tensile strength, large elongation, good self-adhesion, high transparency, strong protection and good cleanliness.

[0003] The materials of the stretch film are mainly PVC, EVA, PE, etc. Among them, PE stretch film is considered to be the main development direction of stretch film production due to its advantages of high production efficiency, good environmental adaptability, high product quality, low price, non-toxic and odorless. Traditional PE stretch film is not easy to decompose due to its poor biodegradability. With the large-scale promotion and use of PE stretch film, the problem of white pollution has also come along. With the demand for low-carbon life, degradable plastic materials are applied. At present, the two mainstream degradable materials are photodegradable materials and biodegradable materials. Among them, photodegradable plastics are limited in application scope because they are only used in areas with long sunshine time and sufficient light, and are mostly limited to farmland covers. The main raw material of PE stretch film, polyolefin, has a large molecular weight and strong hydrophobicity. It biodegrades very slowly in nature. In addition, the conventional PE stretch film has low longitudinal elongation and poor transverse feed strength. It is easy to be broken when wrapping sharp objects, and has poor puncture and tear resistance, which cannot meet large-scale applications. Summary of the invention

[0004] In order to improve the puncture resistance and tear resistance of the PE film and increase the degradation rate of the PE stretch film, the present application provides a fully biodegradable PE stretch film and a preparation process thereof.

[0005] In the first aspect, the present application provides a fully biodegradable PE wrapping film, which adopts the following technical solution:

[0006] A fully biodegradable PE wrapping film, comprising an outer layer, a middle layer and an inner layer laminated in sequence;

[0007] The outer layer comprises the following raw materials in weight percentage: 20-30% No. 1 LLDPE, 63-75% LDPE, 1-3% anti-blocking agent, 2-5% lubricant, and 2-3% degradation masterbatch;

[0008] The middle layer comprises the following raw materials in weight percentage: 30-35% No. 2 LLDPE, 25-35% LDPE, 23-39% MLLDPE, and 1-2% degradation masterbatch;

[0009] The inner layer comprises the following raw materials in weight percentage: 40-45% No. 3 LLDPE, 48-56% LDPE, 3-5% biodegradable tackifying masterbatch and 2-3% degradable masterbatch;

[0010] The density of the No. 1 LLDPE is 0.92 g / cm 3 , the melt index is 2.3g / 10min, and the density of No. 2 LLDPE is 0.918g / cm 3 , the melt index is 2g / 10min, and the density of No. 3 LLDPE is 0.92g / cm 3 , melt index is 1g / 10min;

[0011] The degradable masterbatch comprises the following raw materials in parts by weight: 30-50 parts of PHA, 10-16 parts of cellulose nanofibrils, 2-3.5 parts of algae powder, 1-2 parts of glycerol, 1-2 parts of foaming agent, and 0.1-0.5 parts of nucleating agent.

[0012] By adopting the above technical scheme, the melt index of No. 1 LLDPE in the outer layer and the melt index of No. 2 LLDPE in the middle layer are relatively high, and are greater than the melt index of No. 3 LLDPE in the inner layer. The melt index gradually decreases from the outer to the inner. The melt index of the outer layer is relatively high, and it has higher fluidity during film making, is easier to be stretched and plastic, helps to improve production efficiency, helps to form a more uniform and smoother film layer, and can also improve the wear resistance, tensile resistance and tear resistance of the stretch film, enhance the protective effect of the outer layer on the stretch film, and the high melt index can form The middle layer has a higher melt index than the inner layer, which can help the adhesion between the middle layer, the inner layer and the outer layer, and improve the structural stability of the overall film layer. It can provide certain strength and toughness while maintaining good processing performance and fluidity. The lower melt index of the inner layer LLDPE means that the molecular chain has weaker mobility, which helps to improve the strength and toughness of the stretch film, better withstand external impact and pressure, protect the package from damage, and improve the barrier performance of the film layer to substances such as water vapor and oxygen.

[0013] Degradable masterbatch is added to the outer layer, middle layer and inner layer. The degradable masterbatch is made of cellulose nanofibrils, algae powder, PHA, etc. PHA is polyhydroxyalkanoate, a new type of biodegradable polymer material with physical and chemical properties similar to polymer plastics, and PHA has excellent biodegradability and thermal stability. It can be completely degraded in soil at a temperature of (25±3)°C within about 30 to 60 days, and the degradation rate is very rapid. The addition of foaming agent and nucleating agent can make PHA have uniformly distributed and uniform pores, and the nucleating agent can effectively improve the crystallinity of the material, so that the foamed material can have strong tensile strength and impact strength, high toughness and tear resistance, and the interface between the nucleating agent and PHA can release many low potential energy points, which greatly increases the probability of the appearance of bubble nuclei, and finally the number of pores in the degradable masterbatch is increased, so the contact area with microorganisms is increased, and the degradation rate is increased; cellulose nanofibrils and algae powder It has a high specific surface area and reactive functional groups, and can interact with PHA molecular chains to form a co-crystallization or mechanical interlocking type of tight bonding, thereby enhancing the interaction with the PHA molecular chains, forming more cross-linking points, and increasing the degree of cross-linking. In addition, cellulose nanofibrils have high strength and toughness, and can be used as a reinforcing phase, uniformly dispersed in the PHA matrix, and tightly combined between the PHA molecular chains to form a uniform reinforcement network, improving the tensile strength, bending strength and fracture toughness of the PHA degradation masterbatch. In addition, the active groups contained in the nanofibrils and algae powder are hydrophilic and can be attacked by microorganisms in the water in the soil, causing the microorganisms to adhere to the surface of the PE stretch film and begin to erode. At the same time, the degraded cellulose nanofibrils and algae powder produce a large number of holes and grooves on the surface and inside of the PE stretch film, providing more adsorption sites for organisms, accelerating the covalent bond breakage of the PE stretch film, and enabling the PE stretch film to be quickly biodegraded.

[0014] Optionally, the preparation method of the degradation masterbatch is as follows:

[0015] The cellulose nanofibrils are treated with oxygen plasma, dispersed in deionized water to form a suspension with a concentration of 3-5 wt%, and freeze-dried to obtain a fiber matrix;

[0016] Dissolve the algae powder, add glycerol, mix well to obtain an impregnation solution, soak the fiber matrix in the impregnation solution for 2-4 hours, take out, dry, and crush to obtain matrix powder;

[0017] The base powder is mixed evenly with PHA, a foaming agent and a nucleating agent at 90-100° C., then foamed at 150-160° C. and 15-20 MPa for 5-6 minutes, and then crushed into powder to prepare a degradation masterbatch.

[0018] By adopting the above technical scheme, the cellulose nanofibrils are first treated with oxygen plasma to introduce carboxyl groups and the like on their surface, and the surface roughness is increased and the hydrophilicity is enhanced. When the cellulose nanofibrils are immersed in the impregnation solution, they can react with the carboxyl groups, hydroxyl groups and the like in the algae powder to load the algae powder on the cellulose nanofibrils, and improve the loading fastness between the cellulose nanofibrils and the algae powder. The algae powder on the surface of the cellulose nanofibrils further increases the roughness of the surface of the cellulose nanofibrils, while glycerol can increase the lubricity when the matrix powder is mixed with PHA, a nucleating agent and a foaming agent, and glycerol can also produce hydrogen bonds with the algae powder and the cellulose nanofibrils, so that the dispersibility of the prepared matrix powder in PHA is enhanced and the compatibility is improved, thereby improving the mechanical strength and tensile strength. The degradation masterbatch formed by high-temperature foaming has a porous structure and a large surface area, which allows more water molecules and oxygen to contact the surface of the degradation masterbatch, and can absorb a large amount of water, making it easier for water and oxygen to penetrate into the interior of the degradation masterbatch, accelerating the hydrolysis process, increasing the reaction of microorganisms or enzymes, and accelerating biodegradation. In addition, the surface of the degradation masterbatch obtained by foaming is relatively rough, which is convenient for the attachment and growth of microorganisms, providing more channels for microorganisms and enzymes, making it easier for them to enter the interior of the stretch film for degradation, and also helping to discharge degradation products, thereby further accelerating the biodegradation process. With the degradation of cellulose nanofibrils, algae powder and PHA, the molecular chains in the PE stretch film break, and water and microorganisms enter the interior, thereby accelerating degradation.

[0019] Optionally, the PHA is poly(3-hydroxybutyrate-co-4-hydroxybutyrate).

[0020] By adopting the above technical scheme, the thermal degradation temperature is as high as about 230°C, and it has high thermal stability. The addition of nucleating agent facilitates the wrapping of bubbles by P34HB during the foaming process. Therefore, the degradation masterbatch prepared by foaming has good thermal stability and is not easy to lose the porous structure during melting.

[0021] Optionally, polylactic acid fibers, sodium dodecyl sulfate and gum arabic are further added to the suspension, stirred evenly and then freeze-dried, and the mass ratio of the polylactic acid fibers, sodium dodecyl sulfate, gum arabic to the cellulose nanofibrils is 0.3-0.4:0.28-0.3:1.9-2:1.

[0022] By adopting the above technical scheme, raw materials such as polylactic acid fibers are added to the suspension. The polylactic acid fibers and cellulose nanofibrils have different thicknesses. When mixed with the cellulose nanofibrils, they can be staggered and tightly mixed, while retaining a large number of gaps to increase the porosity, so that the fiber matrix has certain air permeability, and the polylactic acid fibers also have good degradation ability. The addition of polylactic acid fibers can also improve the tensile resistance and toughness of the fiber matrix. The addition of sodium dodecyl sulfate and gum arabic can form bubbles in the suspension during stirring, and the fibers are evenly dispersed and tightly structured. The capillary foam technology generated by stirring gives the polylactic acid fibers and cellulose nanofibrils a skeleton with high yield stress, which can successfully maintain the network structure of the foam. After freeze-drying, a light and porous solid foam fiber matrix is ​​formed, which can improve the porosity in the degradation masterbatch, facilitate the attachment of microorganisms, and increase the degradation rate.

[0023] Optionally, the polylactic acid fiber is made by the following method:

[0024] Dispersing diatom frustules and carboxymethylated Tremella fuciformis polysaccharide in DMF, ultrasonically dispersing at 60-75° C. for 3-5 hours, filtering, washing, and drying to obtain modified diatom frustules;

[0025] The polylactic acid resin and the modified diatom frustules are uniformly mixed and melt-spun to obtain polylactic acid fibers, wherein the mass ratio of the polylactic acid resin to the diatom frustules and the carboxymethylated tremella polysaccharide is 1:0.05-0.1:0.1-0.2.

[0026] By adopting the above technical scheme, the Tremella polysaccharide contains polysaccharides and proteins, and is carboxymethylated to introduce carboxymethyl functional groups into the Tremella polysaccharide through a chemical reaction. The Tremella polysaccharide contains a large number of hydroxyl functional groups. Therefore, after the carboxymethylation modification, the hydroxyl functional groups are partially or completely converted into carboxymethyl functional groups, so that the Tremella polysaccharide contains carboxyl groups, and the Tremella polysaccharide rich in carboxyl groups is obtained; Diatom shell is a natural porous silica material with good thermal stability and a unique multi-level pore structure, and contains highly active silanol groups on the surface, and there is a hydrogen bond in the molecule. Therefore, the Tremella polysaccharide rich in carboxyl groups can interact with the hydroxyl groups on the surface of the diatom shell, so that the diatom shell is rich in carboxyl groups, and the carboxyl functional groups have high reaction activity. The carboxyl groups on the surface of diatom shells and the carboxyl groups in the unreacted carboxymethylated tremella polysaccharide can react with the polylactic acid resin to form chemical bonds, thereby improving the interfacial bonding force, enhancing the tensile properties and impact load resistance of the polylactic acid fiber, and increasing the degradation rate. Therefore, on the one hand, the carboxyl groups on the surface of the carboxymethylated tremella polysaccharide may increase the hydrophilicity of the polylactic acid fiber, thereby facilitating the penetration of water molecules and the degradation process. On the other hand, as an inorganic filler, the carboxymethylated tremella polysaccharide may change the crystallization behavior of polylactic acid and the distribution of amorphous regions, thereby affecting its degradation rate. The diatom shells and the carboxymethylated tremella polysaccharide are dispersed in the PLA slices by melt spinning. The silanol groups on the surface of the diatom shells can form hydrogen bonds with the carbonyl groups on the polylactic acid molecular chain, thereby improving the interaction between the diatom shells and the polylactic acid resin, and the polylactic acid ultrafine nanofibers are obtained after spinning.

[0027] Optionally, the opening agent is porous starch, and the preparation method of the porous starch is as follows:

[0028] Starch, pectin, water and microcrystalline cellulose are mixed in a mass ratio of 80-90:2-4:45:5, kneaded at 90-95°C for 10-15 minutes to obtain a composite, kept at 160-165°C and 18-20MPa for 5-6 minutes, released the pressure, and crushed to obtain a foaming intermediate;

[0029] The foaming intermediate is dispersed in acetonitrile to form an emulsion with a concentration of 1.5-2wt%, succinic acid is dispersed in acetonitrile, heated and stirred to dissolve, added to the emulsion, heated to 75-80°C, kept warm for 20-24h, cooled to 60-65°C, filtered, washed, and dried at 120-125°C. The mass ratio of the foaming intermediate to succinic acid is 1:2.5-3.

[0030] By adopting the above technical solution, the porous starch has a high specific surface area and a porous structure, which enables it to absorb and release oils and fats, and also has good dispersibility. During the production process of the stretch film, it can be evenly dispersed in the film to form tiny particles or holes, reduce the adhesion between plastic stretch films, improve the smoothness and opening properties, make the processing smoother, and the porous structure increases its contact area with the surrounding environment, thereby improving the degradation process.

[0031] By mixing and utilizing the combined effects of mechanical shear, friction and heat, the compatibility of pectin and corn starch is improved, and deep contact, friction and interaction between pectin and starch molecular chains are promoted, thereby inducing esterification cross-linking and forming an esterification cross-linking structure, thereby enhancing the pore wall strength of the porous starch, improving its mechanical tolerance, and improving the pore uniformity of the porous starch, increasing its pore wall thickness, so that the porous starch can better transmit, disperse and withstand compression force, and has good tensile resistance and good rebound and cushioning properties; and since a large number of pore structures are distributed in the starch-based foaming material system, the starch molecular chains in these structures contain a large number of free hydroxyl groups, so the free hydroxyl groups in the pore wall structure of the porous starch can establish hydrogen bonds with water molecules in the environment, so that the porous starch can actively absorb water molecules from the air, showing good hygroscopicity.

[0032] The carboxyl group at one end of succinic acid undergoes esterification reaction with the hydroxyl group in porous starch and is chemically bonded to the surface of porous starch, while the carboxyl group at the other end of succinic acid does not react. The carboxyl functional group has high reactivity, which helps to improve the bonding strength between porous starch and the outer raw material matrix material. In addition, the carboxyl functional group on the surface provides more attachment points and reaction sites for microorganisms, further promoting the degradation of microorganisms.

[0033] Optionally, the density of the LDPE is 0.924 g / cm 3 , melt index is 1.9g / 10min;

[0034] The density of the MLLDPE is 0.918 g / cm 3 , the melt index is 1g / 10min.

[0035] By adopting the above technical solution, LDPE is used in the outer layer, the middle layer and the inner layer, so that the stretch film has strong tear resistance and puncture resistance, while improving the haze and transparency, enhancing the fit with the packaging, and increasing the flatness of the stretch film and the packaging aesthetics; MLLDPE is used in the middle layer, and MLLDPE has higher impact strength and tensile yield strength, so that the stretch film can better maintain its integrity when subjected to external force, is not easy to break or deform, and the melt viscosity is consistent, which can be easier to shape and improve production efficiency.

[0036] Optionally, the foaming agent is selected from at least one of azodicarbonamide, sodium bicarbonate and zinc oxide;

[0037] The nucleating agent is selected from at least one of boron nitride, lignin and calcium carbonate.

[0038] By adopting the above technical scheme, using at least one of azodicarbonamide, sodium bicarbonate and zinc oxide as a foaming agent, the porosity of the degradation masterbatch can be high and the pore size can be smaller, and using at least one of boron nitride and the like as a nucleating agent can improve the mechanical properties and foaming effect of the degradation masterbatch.

[0039] Optionally, the thickness ratio of the outer layer, the middle layer and the inner layer is 3:4:3.

[0040] By adopting the above technical solution, the outer layer, middle layer and inner layer of the stretch film are matched with an appropriate thickness ratio, so that the stretch film is easier to stretch, the operation difficulty is reduced, the packaging efficiency is improved, and it can also play a good buffering role, effectively absorb external impact force, and protect the packaged objects from damage.

[0041] Optionally, the lubricant is selected from polyethylene wax or oleamide;

[0042] The biodegradable tackifying resin is selected from at least one of rosin resin, polymerized rosin, disproportionated rosin, rosin glycol ester, rosin glycerol ester, rosin pentaerythritol ester, terpene resin, polymerized terpene, and terpene-styrene resin.

[0043] By adopting the above technical solution, the lubricant in the outer layer can form a lubricating film on the stretch film, reduce the friction coefficient of the film, and make it easier for the stretch film to slide between layers during packaging, transportation and storage, thereby reducing resistance, improving overall operating efficiency, improving the smoothness of subsequent processing, and enhancing packaging operation efficiency.

[0044] The biodegradable tackifying resin used in the inner layer can significantly improve the adhesion of the inner layer of the stretch film to the packaging, ensuring that the stretch film fits tightly to the surface of the packaging and is not easy to fall off. This adhesion also helps to maintain the stability and integrity of the packaging during transportation and storage, preventing damage or scattering due to loose packaging. In addition, the tackifying resin can enhance the tensile strength, wear resistance and chemical resistance of the stretch film, so that it can better withstand various external forces and environmental factors.

[0045] In the second aspect, the present application provides a preparation process of a fully biodegradable PE wrapping film, which adopts the following technical solution:

[0046] A preparation process of a fully biodegradable PE wrapping film, comprising the following steps: mixing, melting, extruding and granulating a formulated amount of raw materials for preparing an outer layer to prepare an outer layer material, mixing, melting, extruding and granulating a formulated amount of raw materials for preparing a middle layer to prepare a middle layer material, and mixing, melting, extruding and granulating a formulated amount of raw materials for preparing an inner layer to prepare an inner layer material;

[0047] The outer layer material, the middle layer material and the inner layer material are mixed according to a proportion, and then melt-cast into a film, and the melting temperature is 180-200°C.

[0048] By adopting the above technical solution, the raw materials of each layer are first mixed and melt-granulated, which can facilitate the uniform mixing of the components of each layer, so that the uniformity of each layer of the manufactured PE stretch film is better and the thickness is uniform.

[0049] In summary, this application has the following beneficial effects:

[0050] 1. Since the present application adds degradation masterbatch to the mutually bonded outer layer, middle layer and inner layer, and the degradation masterbatch is made by foaming PHA, cellulose nanofibrils, algae powder, glycerin, etc. at appropriate temperature and pressure, the prepared degradation masterbatch has a large surface area, high porosity, high tensile strength and impact strength, and strong puncture resistance. In addition, the cellulose nanofibrils and algae powder make the degradation masterbatch more hydrophilic, which is more conducive to the attachment and binding of microorganisms. With the decomposition and degradation of cellulose nanofibrils and algae powder, the roughness of the degradation masterbatch increases, and a large number of holes or grooves are gradually generated on the surface and inside of the wrapping film, which is more conducive to the biodegradation and can gradually complete the full biodegradation of the wrapping film.

[0051] 2. In the present application, polylactic acid fibers, sodium dodecyl sulfate and gum arabic are preferably added to the suspension formed by cellulose nanofibrils. After being stirred evenly, bubbles are generated, which increases the porosity of the fiber matrix. Moreover, the polylactic acid fibers and cellulose nanofibrils have different thicknesses, which increase the air permeability and porosity while being tightly combined, thereby increasing the attachment sites of microorganisms and accelerating the rate of biodegradation.

[0052] 3. In the present application, it is preferred to prepare modified diatom frustules by mixing diatom frustules and carboxymethylated tremella polysaccharide, and utilize carboxymethylated tremella polysaccharide to interact with hydroxyl groups in diatom frustules to improve the binding force between diatom frustules and polylactic acid, and enhance the mechanical strength of polylactic acid fibers. At the same time, in the preparation of polylactic acid fibers by melt spinning, carboxymethylated tremella polysaccharide can also improve its hydrophilicity and crystallinity, and improve the degradation rate and mechanical strength of polylactic acid. DETAILED DESCRIPTION

[0053] The following examples further illustrate the present application in detail.

[0054] Preparation Example 1: (1) 16 g of cellulose nanofibrils were treated with oxygen plasma, then dispersed in deionized water to form a suspension with a concentration of 5 wt%, and freeze-dried at -65 °C for 36 h to obtain a fiber matrix. The cellulose nanofibrils were selected from Guangzhou Zelong Chemical Technology Co., Ltd., with a product number of ZR-19. The oxygen plasma treatment power was 45 W and the treatment time was 10 min.

[0055] (2) 3.5 g of algae powder was dissolved in 30 g of deionized water, and 2 g of glycerol was added to prepare an impregnation solution. The fiber matrix was immersed in the impregnation solution for 4 h, and then dried at 60 ° C for 10 h and crushed to obtain a matrix powder with a particle size of 20 μm. The algae powder was spirulina powder selected from Shaanxi Snotech Biotechnology;

[0056] (3) The prepared matrix powder was mixed evenly with 50 g PHA, 2 g foaming agent, and 0.5 g nucleating agent, and then foamed at 160 ° C and 20 MPa for 5 min, and then crushed into a powder with a particle size of 5 μm. The PHA was P34HB, selected from Shandong Yikeman, model P34HB-10, the nucleating agent was boron nitride, and the foaming agent was sodium bicarbonate.

[0057] Preparation Example 2: (1) 10 g of cellulose nanofibrils were treated with oxygen plasma, then dispersed in deionized water to form a suspension with a concentration of 3 wt%, and freeze-dried at -65 °C for 36 h to obtain a fiber matrix. The cellulose nanofibrils were selected from Guangzhou Zelong Chemical Technology Co., Ltd., with a product number of ZR-19. The oxygen plasma treatment power was 50 W and the treatment time was 5 min.

[0058] (2) 2 g of algae powder was dissolved in 30 g of deionized water, and 1 g of glycerol was added to prepare an impregnation solution. The fiber matrix was immersed in the impregnation solution for 2 h, and then dried at 60 ° C for 10 h, and crushed to obtain a matrix powder with a particle size of 20 μm. The algae powder was spirulina powder selected from Shaanxi Snotech Biotechnology;

[0059] (3) The prepared matrix powder was mixed evenly with 30 g PHA, 1 g foaming agent, and 0.1 g nucleating agent, and then foamed at 150 ° C and 15 MPa for 6 min, and then crushed into a powder with a particle size of 5 μm. The PHA was P34HB, selected from Shandong Yikeman, model P34HB-10, the nucleating agent was calcium carbonate, and the foaming agent was azodicarbonamide.

[0060] Preparation Example 3: The difference from Preparation Example 1 is that cellulose nanofibrils, algae powder and glycerol are not added, 50g PHA, 2g foaming agent and 0.5g nucleating agent are mixed evenly, then foamed at 160°C and 20MPa for 5min, and then crushed into powder with a particle size of 5μm, PHA is P34HB, selected from Shandong Yikeman, model P34HB-10, nucleating agent is boron nitride, and foaming agent is sodium bicarbonate.

[0061] Preparation Example 4: The difference from Preparation Example 1 is that the impregnation solution made of algae powder and glycerol is not used for impregnation. (1) 16g of cellulose nanofibrils are treated with oxygen plasma and then dispersed in deionized water to form a suspension with a concentration of 5wt%, and freeze-dried at -65°C for 36h to obtain a fiber matrix. The cellulose nanofibrils are selected from Guangzhou Zelong Chemical Technology Co., Ltd., with a product number of ZR-19. The oxygen plasma treatment power is 45W and the treatment time is 10min. (2) The fiber matrix is ​​evenly mixed with 50g PHA, 2g foaming agent, and 0.5g nucleating agent, and then foamed at 160°C and 20MPa for 5min, and then crushed into a powder with a particle size of 5μm. PHA is P34HB, selected from Shandong Yikeman, with a model number of P34HB-10. The nucleating agent is boron nitride and the foaming agent is sodium bicarbonate.

[0062] Preparation Example 5: The difference from Preparation Example 1 is that 16g of cellulose nanofibrils, 3.5g of algae powder, 2g of glycerol, 50g of PHA, 2g of foaming agent, and 0.5g of nucleating agent are evenly mixed, then foamed at 160°C and 20MPa for 5min, and then crushed into a powder with a particle size of 5μm, the PHA is P34HB, selected from Shandong Yikeman, model P34HB-10, the nucleating agent is boron nitride, and the foaming agent is sodium bicarbonate.

[0063] Preparation Example 6: The difference from Preparation Example 1 is that no foaming agent and nucleating agent are added, the base powder is mixed evenly with 50g PHA at 100°C, and then extruded and granulated at 160°C. The PHA is P34HB, selected from Shandong Yikeman, model P34HB-10.

[0064] Preparation Example 7: The difference from Preparation Example 1 is that in step (1), 6.4 g of polylactic acid fiber, 4.48 g of sodium dodecyl sulfate and 30.4 g of gum arabic are further added to the suspension, and the mixture is stirred at 2000 rpm for 15 min and then freeze-dried. The polylactic acid fiber is prepared by the following method: ① Disperse 10 g of diatom shells and 20 g of carboxymethylated tremella polysaccharide in 100 ml of DMF, ultrasonically disperse at 60°C for 5 h, filter, wash with deionized water 5 times, and dry at 80°C to obtain modified diatom shells. The preparation method of diatom shells is as follows: oxidize the diatom with 30% hydrogen peroxide solution for 12 h, place it in 1 mol / l hydrochloric acid solution for acidification for 24 h, wash it with water 5 times, and then calcine it at 600°C in an oxygen atmosphere. ② Mix 100g of polylactic acid resin and modified diatom shells evenly and melt-spin to obtain polylactic acid fiber. The spinning temperature is 185°C. The mass ratio of polylactic acid resin, diatom shells and carboxymethylated tremella polysaccharide is 1:0.1:0.2. The polylactic acid resin is selected from Total of Thailand with the item number LX930. The preparation method of carboxymethylated tremella polysaccharide is as follows: soak 20g of tremella polysaccharide in 200ml of 85% ethanol, add 6.82g of sodium hydroxide and react at 50°C for 2h, add 6,8 ​​sodium hydroxide and 18.9g of monochloroacetic acid, react at 60°C for 6h, adjust the pH to 7 with acetic acid, add 80% ethanol to obtain a precipitate, and dry it at 45°C.

[0065] Preparation Example 8: The difference from Preparation Example 1 is that in step (1), 4.8 g of polylactic acid fiber, 4.8 g of sodium dodecyl sulfate and 32 g of gum arabic are further added to the suspension, and the suspension is stirred at 2000 rpm for 15 min and then freeze-dried, wherein the polylactic acid fiber is prepared by the following method: ① Disperse 5 g of diatom shells and 10 g of carboxymethylated Tremella polysaccharide into 100 ml ② The diatom shells were ultrasonically dispersed in DMF at 75 ° C for 3 h, filtered, washed with deionized water for 5 times, and dried at 80 ° C to obtain modified diatom shells. The preparation method of diatom shells was as follows: the diatoms were oxidized with 30% hydrogen peroxide solution for 12 h, placed in a 1 mol / l hydrochloric acid solution for acidification for 24 h, washed with water 5 times, sintered at 600 ° C in an oxygen atmosphere for 2 h, and ball milled at a speed of 120 r / min for 0.5 h; ② 100 g of polylactic acid resin was mixed evenly with the modified diatom shells, and melt-spun to obtain polylactic acid fibers. The spinning temperature was 185 ℃, the mass ratio of polylactic acid resin, diatom shell and carboxymethylated tremella polysaccharide is 1:0.05:0.1, the polylactic acid resin is selected from Total of Thailand, the product number is LX930, and the preparation method of carboxymethylated tremella polysaccharide is as follows: 20g tremella polysaccharide is soaked in 200ml ethanol with a concentration of 85%, 6.82g sodium hydroxide is added and reacted at 50℃ for 2h, 6,8 sodium hydroxide and 18.9g monochloroacetic acid are added, and the reaction is carried out at 60℃ for 6h, the pH is adjusted to 7 with acetic acid, 80% ethanol is added to obtain a precipitate, and it is dried at 45℃.

[0066] Preparation Example 9: The difference from Preparation Example 7 is that sodium lauryl sulfate and gum arabic are not added.

[0067] Preparation Example 10: The difference from Preparation Example 7 is that polylactic acid fiber is not added.

[0068] Preparation Example 11: The difference from Preparation Example 7 is that no diatom frustules and carboxymethylated tremella polysaccharide are added to the polylactic acid fiber, and the polylactic acid fiber is only made of polylactic acid resin by melt spinning.

[0069] Preparation Example 12: The difference from Preparation Example 7 is that diatom frustules are used in an equal amount to replace carboxymethylated Tremella polysaccharide in the polylactic acid fiber.

[0070] Preparation Example 13: The difference from Preparation Example 7 is that the Tremella polysaccharide is not subjected to carboxymethylation treatment.

[0071] Preparation Example 14: 90 g of corn starch, orange pectin, deionized water and microcrystalline cellulose in a mass ratio of 90:2:45:5 were mixed, kneaded at 95° C. for 10 min to obtain a composite, and then kept at 165° C. and 18 MPa for 6 min, released the pressure, and crushed to obtain porous starch.

[0072] Preparation Example 15: 90 g of corn starch, orange pectin, deionized water and microcrystalline cellulose in a mass ratio of 90:2:45:5 were mixed, kneaded at 95° C. for 10 min to obtain a composite, and then kept at 165° C. and 18 MPa for 6 min, released the pressure, and crushed to obtain a foaming intermediate;

[0073] Disperse 10g of the foaming intermediate in acetonitrile to form an emulsion with a concentration of 2wt%, disperse 30g of succinic acid in 500ml of acetonitrile, heat and stir to dissolve, add the emulsion, heat to 75°C, keep warm for 24h, cool to 65°C, filter, wash with anhydrous ethanol and deionized water 3 times each, dry at 120°C, the mass ratio of the foaming intermediate to succinic acid is 1:3.

[0074] Preparation Example 16: Corn starch, orange pectin, deionized water and microcrystalline cellulose in a mass ratio of 80:2:45:5 were mixed, kneaded at 95° C. for 10 min to obtain a composite, and then kept at 160° C. and 20 MPa for 5 min, released the pressure, and crushed to obtain a foaming intermediate;

[0075] Disperse 10g of the foaming intermediate in acetonitrile to form an emulsion with a concentration of 1.5wt%, disperse 25g of succinic acid in 500ml of acetonitrile, heat and stir to dissolve, add the emulsion, heat to 80°C, keep warm for 20h, cool to 60°C, filter, wash with anhydrous ethanol and deionized water three times each, and dry at 125°C. The mass ratio of the foaming intermediate to succinic acid is 1:2.5. Example

[0076] Example 1: A fully biodegradable PE wrapping film, comprising an outer layer, a middle layer and an inner layer laminated in sequence with a mass ratio of 3:4:3, and the raw material proportions of the outer layer, the middle layer and the inner layer are shown in Table 1. The melt index (190°C, 2.16kg) of No. 1 LLDPE in the outer layer is 2.3g / 10min, and the density is 0.92g / cm 3 , selected from Liaotong Chemical Industry, brand LL0220AA, density of No. 2 LLDPE is 0.198g / cm 3 , melt index (190℃, 2.16kg) is 2g / 10min, selected from Exxon, brand 1002BU, density of No. 3 LLDPE is 0.92g / cm 3 , melt index (190℃, 2.16kg) is 1g / 10min, selected from Dow Chemical, USA, brand 2045G, LDPE density is 0.925g / cm 3 , melt index (190℃, 2.16kg) is 1.9g / 10min, selected from CNOOC Shell, brand 2420H, MLLDPE density is 0.918g / cm 3 , the melt index (190°C, 2.16kg) is 1g / 10min, the brand is DowDuPont, the brand is 5401G, the opening agent is erucamide, the lubricant is polyethylene wax, the biodegradable tackifying masterbatch is rosin resin, and the degradable masterbatch is made by Preparation Example 1.

[0077] The preparation process of the above-mentioned fully biodegradable PE stretch film comprises the following steps:

[0078] According to the raw material dosage in Table 1, the outer layer raw materials were mixed, melted and granulated at 160°C to obtain the outer layer material, the middle layer raw materials were mixed, melted and granulated at 160°C to obtain the middle layer material, and the inner layer raw materials were mixed, melted and granulated at 160°C to obtain the inner layer material;

[0079] The outer layer material, the middle layer material and the inner layer material are mixed according to the ratio, and then melt-cast into a film to obtain a winding film with a thickness of 19 μm, the melting temperature is 180°C, the casting roller speed is 1.2 m / min, the pulling roller speed is 1.4 m / min, the pulling roller synchronization coefficient is 1.2, the winding roller tension is 2.8 kg, the winding roller synchronization coefficient is 0.4, and the cooling roller temperature is 30°C.

[0080] Table 1 Raw material dosage of fully biodegradable PE wrapping film in Examples 1-3

[0081]

[0082] Example 2: A fully biodegradable PE wrapping film, which differs from Example 1 in that the raw material proportions of the outer layer, the middle layer and the inner layer are as shown in Table 1, and the degradation masterbatch is made from Preparation Example 2.

[0083] The preparation process of the above-mentioned fully biodegradable PE stretch film comprises the following steps:

[0084] According to the raw material dosage in Table 1, the outer layer raw materials were mixed, melted and granulated at 170°C to obtain the outer layer material, the middle layer raw materials were mixed, melted and granulated at 170°C to obtain the middle layer material, and the inner layer raw materials were mixed, melted and granulated at 170°C to obtain the inner layer material;

[0085] The outer layer material, the middle layer material and the inner layer material are mixed according to the ratio, and then melt-cast into a film to obtain a winding film with a thickness of 19 μm, the melting temperature is 200°C, the casting roller speed is 0.8 m / min, the pulling roller speed is 1.1 m / min, the pulling roller synchronization coefficient is 1.5, the winding roller tension is 3.5 kg, the winding roller synchronization coefficient is 0.4, and the cooling roller temperature is 20°C.

[0086] Example 3: A fully biodegradable PE wrapping film, which is different from Example 1 in that the raw material proportions of the outer layer, the middle layer and the inner layer are as shown in Table 1.

[0087] Example 4: A fully biodegradable PE wrapping film, which is different from Example 1 in that the biodegradable masterbatch in the outer layer, the middle layer and the inner layer is made from Preparation Example 7.

[0088] Example 5: A fully biodegradable PE wrapping film, which is different from Example 1 in that the biodegradable masterbatch in the outer layer, the middle layer and the inner layer is made from Preparation Example 8.

[0089] Example 6: A fully biodegradable PE wrapping film, which is different from Example 4 in that the biodegradable masterbatch in the outer layer, the middle layer and the inner layer is made from Preparation Example 9.

[0090] Example 7: A fully biodegradable PE wrapping film, which is different from Example 4 in that the biodegradable masterbatch in the outer layer, the middle layer and the inner layer is made from Preparation Example 10.

[0091] Example 8: A fully biodegradable PE wrapping film, which is different from Example 4 in that the biodegradable masterbatch in the outer layer, the middle layer and the inner layer is made from Preparation Example 11.

[0092] Example 9: A fully biodegradable PE wrapping film, which is different from Example 4 in that the biodegradable masterbatch in the outer layer, the middle layer and the inner layer is made from Preparation Example 12.

[0093] Example 10: A fully biodegradable PE wrapping film, which differs from Example 4 in that the biodegradable masterbatch in the outer layer, the middle layer and the inner layer is made from Preparation Example 13.

[0094] Example 11: A fully biodegradable PE wrapping film, which differs from Example 4 in that the opening agent in the outer layer is porous starch, and the porous starch is made by Preparation Example 14.

[0095] Example 12: A fully biodegradable PE wrapping film, which differs from Example 4 in that the opening agent in the outer layer is porous starch, and the porous starch is made by Preparation Example 15.

[0096] Example 13: A fully biodegradable PE wrapping film, which differs from Example 4 in that the opening agent in the outer layer is porous starch, and the porous starch is made from Preparation Example 16.

[0097] Comparative Example 1: A fully biodegradable PE wrapping film, which is different from Example 1 in that the degradation masterbatch is made from Preparation Example 3.

[0098] Comparative Example 2: A fully biodegradable PE wrapping film, which is different from Example 1 in that the degradation masterbatch is made from Preparation Example 4.

[0099] Comparative Example 3: A fully biodegradable PE wrapping film, which is different from Example 1 in that the degradation masterbatch is made from Preparation Example 5.

[0100] Comparative Example 4: A fully biodegradable PE wrapping film, which differs from Example 1 in that the degradation masterbatch is made from Preparation Example 6.

[0101] Comparative Example 5: A fully biodegradable PE wrapping film, which differs from Example 1 in that No. 3 LLDPE is replaced by No. 1 LLDPE in the inner layer. The melt index (190°C, 2.16kg) of No. 1 LLDPE is 2.3g / 10min and the density is 0.92g / cm 3 , selected from Liaotong Chemical Industry, brand LL0220AA.

[0102] Comparative Example 6: A fully biodegradable PE wrapping film, which is different from Example 1 in that No. 1 LLDPE is replaced by No. 3 LLDPE in the outer layer, and the density of No. 3 LLDPE is 0.92 g / cm 3 The melt index (190°C, 2.16kg) is 1g / 10min. It is selected from Dow Chemical of the United States and the brand is 2045G.

[0103] PE stretch films were prepared according to the methods in the examples and comparative examples, and performance tests were performed according to the following methods. The test results are recorded in Table 2.

[0104] 1. Tensile strength and elongation at break: The test was conducted in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", with a measuring speed of 10 mm / s. Three groups of tests were conducted for each embodiment or comparative example, and the average value was taken.

[0105] 2. Impact strength: Tested in accordance with GB / T1843-2008, the test speed is 3.5m / s, 3 groups are tested and the average value is taken.

[0106] 3. Water absorption rate: Cut the film into 2cm×2cm pieces and place it in 30 mL of distilled water at room temperature until the film completely absorbs water. Use absorbent paper to absorb the water on the surface of the film and weigh it. Test the mass before and after water absorption and calculate the water absorption rate.

[0107] 4. Biodegradation test: The natural soil landfill method is used for determination. 10g of 10mm×10 mm sample is placed in a 100mm×100mm×100mm soil pit, and the sample is 10mm away from the soil. The soil selected is loose farmland, the soil pH value is 6-8, and the humidity is greater than 80%. The experiment is carried out in the open air; after different landfill times, the weight of the remaining sample is measured to determine its biodegradability, and the weight loss rate (%) = (initial sample mass-remaining sample weight) / initial sample mass×100.

[0108] Table 2 Performance test of fully biodegradable PE wrapping film

[0109]

[0110] Combining the data in Table 2 with the raw material selection in Examples 1-3, it can be seen that the PE wrapping film prepared in Examples 1-3 using the degradable masterbatch prepared in Preparation Example 1 and Preparation Example 2 has strong initial tensile strength and puncture resistance, high water absorption, good biodegradability, and can be degraded by more than 90% within 12 weeks. The degradation speed is fast and can be completely degraded as time goes by.

[0111] Compared with Example 1, Example 4 and Example 5 respectively use the degradation masterbatch prepared in Preparation Example 7 and Preparation Example 8. Compared with Example 1, Preparation Example 7 and Preparation Example 8 also add polylactic acid fiber, sodium dodecyl sulfate and gum arabic into the fiber matrix. It can be seen that the mechanical strength of the prepared PE wrapping film is increased, and the impact resistance and tear resistance are enhanced. In addition, the water absorption rate is increased, it is more hydrophilic, easier to degrade, and the biodegradation rate is increased.

[0112] Compared with Example 4, Example 6 adopts the degradation masterbatch prepared in Preparation Example 9. Compared with Preparation Example 8, Preparation Example 9 does not add sodium dodecyl sulfate and gum arabic. Table 2 shows that the PE wrapping film prepared in Example 6 has a lower water absorption rate and a reduced degradation rate, indicating that freeze-drying of sodium dodecyl sulfate and gum arabic after stirring can increase the bubble content, improve the porosity in the fiber matrix, and thus enhance the water absorption rate and improve the degradation rate.

[0113] Compared with Example 4, Example 7 uses the degradation masterbatch made in Preparation Example 10, in which no polylactic acid fiber is added. It can be seen that the tensile strength and impact strength of the PE wrapping film made therefrom are significantly reduced, the water absorption rate is reduced, and the biodegradation rate is slowed down.

[0114] In Example 8, the degradation masterbatch prepared in Preparation Example 11 was used. Compared with Preparation Example 7 in Example 4, diatom frustules and carboxylated tremella polysaccharide were not added to the polylactic acid fiber in Preparation Example 11. It can be seen that the tensile and puncture resistance of the PE wrapping film prepared in Example 8 were reduced, and the degradation rate was slowed down, indicating that adding diatom frustules and carboxymethylated polysaccharides to the polylactic acid fiber can improve the crystallinity of polylactic acid, enhance the tensile resistance of the polylactic acid fiber, and increase the degradation rate.

[0115] In Example 9, the degradation masterbatch prepared in Preparation Example 12 was used. Compared with Example 4, diatom frustules were used in Preparation Example 12 instead of carboxymethylated tremella polysaccharide, while in Example 10, the degradation masterbatch prepared in Preparation Example 13 was used, in which the tremella polysaccharide was not carboxymethylated. It can be seen that in the PE wrapping film materials prepared in Examples 9 and 10, the amount of diatom frustules in Example 9 was increased. Although the degradation rate of the PE wrapping film increased, it had an adverse effect on the tensile strength of the polylactic acid fiber, etc., causing the mechanical strength of the PE wrapping film to decrease. In Example 10, the mechanical strength and mixed water absorption of the wrapping film did not change much, but the degradation rate was slowed down.

[0116] In Example 11, the porous starch prepared in Preparation Example 14 is used as an opening agent. The porous starch is made of corn starch, orange pectin, etc. through heat preservation and foaming. Compared with the use of erucamide in Example 4, the water absorption rate of the PE wrapping film is slightly improved, and the degradation rate is increased.

[0117] Compared with Example 4, Example 12 and Example 13 respectively use the porous starch prepared in Preparation Example 14 and Preparation Example 15 as the opening agent, and use succinic acid to modify the porous starch. The degradation ability of the PE wrapping film prepared in Example 12 and Example 13 is further enhanced.

[0118] In Comparative Example 1, the degradation masterbatch prepared in Preparation Example 3 was used. Compared with Preparation Example 1, cellulose nanofibrils and algae powder were not added. PHA was blended with a foaming agent and a nucleating agent for foaming. It can be seen that the tensile properties of the PE wrapping film deteriorated, the water absorption rate decreased, and the degradation rate slowed down.

[0119] In Comparative Example 2, the degradation masterbatch prepared in Preparation Example 4 was used. Compared with Example 1, algae powder and glycerol were not used to soak the fiber matrix. In Comparative Example 3, the degradation masterbatch prepared in Preparation Example 5 was used. Compared with Preparation Example 1, cellulose nanofibrils were blended and foamed with PHA, etc. It can be seen from the data in Table 2 that the tensile strength of the PE wrapping films prepared in Comparative Examples 2 and 3 did not change much, but the water absorption rate decreased and the degradation rate slowed down.

[0120] Comparative Example 4 uses the degradation masterbatch prepared in Preparation Example 6. Compared with Preparation Example 1, no foaming agent and nucleating agent are added. Compared with Example 1, the tensile strength and elongation at break of the PE wrapping film prepared in Comparative Example 4 are reduced, the impact strength is weakened, the water absorption rate is significantly reduced, and the degradation rate is slowed down.

[0121] Compared with Example 1, Comparative Examples 5 and 6 respectively change the melt index of LLDPE in the inner layer and the outer layer. It can be seen that the tensile strength and other properties of the PE wrapping film are reduced, and the puncture resistance is weakened.

[0122] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fully biodegradable PE stretch film, characterized in that: It includes an outer layer, a middle layer and an inner layer which are laminated in sequence; The outer layer comprises the following raw materials in weight percentage: 20-30% No. 1 LLDPE, 63-75% LDPE, 1-3% anti-blocking agent, 2-5% lubricant, and 2-3% degradation masterbatch; The middle layer comprises the following raw materials in weight percentage: 30-35% No. 2 LLDPE, 25-35% LDPE, 23-39% MLLDPE, and 1-2% degradation masterbatch; The inner layer comprises the following raw materials in weight percentage: 40-45% No. 3 LLDPE, 48-56% LDPE, 3-5% biodegradable tackifying resin and 2-3% degradation masterbatch; The density of the No. 1 LLDPE is 0.92 g / cm 3 , the melt index is 2.3g / 10min, and the density of No. 2 LLDPE is 0.918g / cm 3 , the melt index is 2g / 10min, and the density of No. 3 LLDPE is 0.92g / cm 3 , melt index is 1g / 10min; The degradable masterbatch comprises the following raw materials in parts by weight: 30-50 parts of PHA, 10-16 parts of cellulose nanofibrils, 2-3.5 parts of algae powder, 1-2 parts of glycerol, 1-2 parts of foaming agent, and 0.1-0.5 parts of nucleating agent; The preparation method of the degradation masterbatch is as follows: The cellulose nanofibrils are treated with oxygen plasma, dispersed in deionized water to form a suspension with a concentration of 3-5 wt%, and freeze-dried to obtain a fiber matrix; Dissolve the algae powder, add glycerol, mix well to obtain an impregnation solution, soak the fiber matrix in the impregnation solution for 2-4 hours, take out, dry, and crush to obtain matrix powder; The base powder is mixed evenly with PHA, a foaming agent and a nucleating agent at 90-100° C., then foamed at 150-160° C. and 15-20 MPa for 5-6 minutes, and then crushed into powder to prepare a degradation masterbatch.

2. The fully biodegradable PE stretch film according to claim 1, characterized in that: Polylactic acid fiber, sodium lauryl sulfate and gum arabic are also added to the suspension, which is evenly stirred and then freeze-dried. The mass ratio of the polylactic acid fiber, sodium lauryl sulfate, gum arabic and cellulose nanofibrils is 0.3-0.4:0.28-0.3:1.9-2:

1.

3. The fully biodegradable PE stretch film according to claim 2, characterized in that: The polylactic acid fiber is made by the following method: Dispersing diatom frustules and carboxymethylated Tremella fuciformis polysaccharide in DMF, ultrasonically dispersing at 60-75° C. for 3-5 hours, filtering, washing, and drying to obtain modified diatom frustules; The polylactic acid resin and the modified diatom frustules are uniformly mixed and melt-spun to obtain polylactic acid fibers, wherein the mass ratio of the polylactic acid resin to the diatom frustules and the carboxymethylated tremella polysaccharide is 1:0.05-0.1:0.1-0.

2.

4. The fully biodegradable PE stretch film according to claim 1, characterized in that: The opening agent is porous starch, and the preparation method of the porous starch is as follows: Starch, pectin, water and microcrystalline cellulose are mixed in a mass ratio of 80-90:2-4:45:5, kneaded at 90-95°C for 10-15 minutes to obtain a composite, kept at 160-165°C and 18-20MPa for 5-6 minutes, released the pressure, and crushed to obtain a foaming intermediate; The foaming intermediate is dispersed in acetonitrile to form an emulsion with a concentration of 1.5-2wt%, succinic acid is dispersed in acetonitrile, heated and stirred to dissolve, added to the emulsion, heated to 75-80°C, kept warm for 20-24h, cooled to 60-65°C, filtered, washed, and dried at 120-125°C. The mass ratio of the foaming intermediate to succinic acid is 1:2.5-3.

5. The fully biodegradable PE stretch film according to claim 1, characterized in that: The density of the LDPE is 0.924 g / cm 3 , melt index is 1.9g / 10min; The density of the MLLDPE is 0.918 g / cm 3 , the melt index is 1g / 10min.

6. The fully biodegradable PE stretch film according to claim 1, characterized in that: The foaming agent is selected from at least one of azodicarbonamide, sodium bicarbonate and zinc oxide; The nucleating agent is selected from at least one of boron nitride, lignin and calcium carbonate.

7. The fully biodegradable PE stretch film according to claim 1, characterized in that: The thickness ratio of the outer layer, the middle layer and the inner layer is 3:4:

3.

8. The fully biodegradable PE stretch film according to claim 1, characterized in that: The lubricant is selected from polyethylene wax or oleic acid amide; The biodegradable tackifying resin is selected from at least one of rosin resin, polymerized rosin, disproportionated rosin, rosin glycol ester, rosin glycerol ester, rosin pentaerythritol ester, terpene resin, polymerized terpene, and terpene-styrene resin.

9. The process for preparing the fully biodegradable PE wrapping film according to any one of claims 1 to 8, characterized in that: The following steps are involved: The outer layer material is prepared by mixing, melting, extruding and granulating the raw materials for the outer layer in the formula amount, the middle layer material is prepared by mixing, melting, extruding and granulating the raw materials for the middle layer in the formula amount, and the inner layer material is prepared by mixing, melting, extruding and granulating the raw materials for the inner layer in the formula amount; The outer layer material, the middle layer material and the inner layer material are mixed according to a proportion, and then melt-cast into a film, and the melting temperature is 180-200°C.

Citation Information

Patent Citations

  • Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) foaming material and preparation method thereof

    CN104448745A

  • Degradable foaming package material and preparation method thereof

    CN107418169A